Desenvolvimento de nanocarreadores a base de piperina: influência do polímero e citotoxicidade in vitro – in vivo - Motta, Mariana Heldt (2016)
This study aimed the development of nanoemultions and polymeric nanocapsule suspensions containing piperine, in order to study their considering photodegradation and citotoxicity. To quantify piperine at the nanostructures, at first, a liquid chromatography analytical methodology was validated. The method was specific, linear, precise, exact and robust. The nanoemultions and nanocapsules containing the bioactive (1.0 mg/mL) were prepared by the spontaneous emulsification method and the interfacial deposition of preformed polymer, respectively. For the physic-chemical characterization of formulations, the average diameter of particles, the polydispersion index, pH, zeta potential, bioactive concentration and the encapsuling efficiency were evaluated. The nanostructures presented nanometric size (170 to 210 nm), polydispersion index below 0.12, acid pH (5.8 to 6.4), negative zeta potential (-6.3 to -12.4 mV), piperine concentration and encapsuling efficiency close to 100%. About stability, pH values and the bioactive concentration were affected during the 90 days period, of storage. The photodegradation study of piperine against the UVA light ratified the nanostructures systems capacity in supporting the photoprotection of substances, and showed a higher protection for the nanocapsules when compared to the nanoemultions. A release study was conducted using gastrointestinal simulated media, it was applied a method of diffusion in dialysis bags. The nanostructures showed a lower release among the different analysis times in comparison non-encapsulated bioactive. For the citotoxicity in vitro assays, the evaluation of anti tumor activity has been done through MTT in HepG2, HT-29 and fibroblasts cells. The toxicity of piperine to cancer cells was shown to be greater when it was associated with nanostructures, than in the free form (not associated to the nanocarriers), and also, to a higher cellular viability related to the fibroblasts. The in vivo assay, carried out with C. elegans, evaluated the toxicity and the survivability in juglone (antioxidant capacity). Faringeos beatings were not affected and the defecation was not affected only in the formulations without the bioactive presence, confirming the ingestion of piperine by the worm and the non-toxicity of the particles. For the survivability study against the juglone, the nanoemultions containing piperine and the bioactive in solution presented the significant lowering of mortality taxes in comparisons to the control group, showing antioxidant action, since they protected the oxidative damage (caused by the superoxide), caused by the juglone. Contrary to nanocapsules, which didn't showed effect, probably because because of polymeric wall limitation, reducing the bioactive release and the further desired action for this experiment.